Forecasting the 2015 general election using aggregate local election data. (March 2016) - Rallings, Colin; Thrasher, Michael; Borisyuk, Galina
Abstract: Local government election results are used to estimate a national equivalent vote that provides the basis for a general election forecast. By-elections provide the means for calculating weighted quarterly averages of national support. These show trends similar to those obtained by national polls. By-election results in the three month period leading to the general election contribute towards the national vote share calculation and seat distributions are determined by uniform national swing. Additionally, results from the main council elections from 2011 onwards are aggregated to the parliamentary constituency level and used to estimate each party's relative performance in key target seats. This information is used to fine-tune the final seat forecast which suggests a hung parliament is the most likely outcome. Highlights: Local council by-elections are used to produce estimates of national party vote share. Trends in local voting support conform with evidence produced by national survey data. By-elections prior to the general election suggest equal shares for two main parties. The model indicates a loss of votes and seats for the Liberal Democrats. The model indicates a rise in votes for the United Kingdom Independence Party.